Why civilians don't defer to military preferences about cyber strategy like they do for other domains. - Lonergan, Erica D. (Journal of Strategic Studies, 2025)
Do civilians defer to military preferences about U.S. cyber strategy? The civil-military relations literature has only cursorily addressed this question. This article aims to fill this gap. I argue that three factors affect the prospects of civilian deference: secrecy, the relative bureaucratic power of U.S. Cyber Command, and the influence of civilian industry. Taken together, these factors make civilians less likely to excessively defer to the military. I examine more than a decade of strategy, doctrine, and public discourse among U.S. civilian and military leaders about military cyber power, and find limited evidence of excessive civilian deference.